2007
DOI: 10.1007/s11270-007-9467-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Rain and Fog Water in the Cervenohorske Sedlo (Hruby Jesenik Mountains, Czech Republic)

Abstract: Field study at the Cervenohorske sedlo (1,013 m a.s.l.) (Hruby Jesenik Mountains, the Czech Republic, Central Europe) during 1999-2002 has been conducted in order to analyse the chemistry of rain/ snow water using bulk and throughfall collector and fog/cloud water using modified passive Grunow collector. Fog water input to coniferous forest (Picea abies) was quantified using canopy balance method. For all samples pH, and the concentrations of NH þ 4 , Ca 2+ , K + , Mg 2+ , Na + , Cl − , NO À 3 , and SO 2À 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…SO 4 2-ions were measured as 5.05-6.80 and 5.03-7.06 mg/L in UR and BZ samples, respectively. These values are in good agreement with the data reported by Zapletal et al (2007). NO 3 -was estimated as < 0.1-10.86 and < 0.1-2.92 mg/L in UR and BZ samples.…”
Section: Chemical Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…SO 4 2-ions were measured as 5.05-6.80 and 5.03-7.06 mg/L in UR and BZ samples, respectively. These values are in good agreement with the data reported by Zapletal et al (2007). NO 3 -was estimated as < 0.1-10.86 and < 0.1-2.92 mg/L in UR and BZ samples.…”
Section: Chemical Compositionsupporting
confidence: 92%
“…Pollution monitoring through the estimation of air pollutants in wet deposition has increased during the last decades (Zapletal et al, 2007;Holder, 2004). Fog in the metropolitan area of Karachi occurs during the winter season (November to March).…”
Section: Introductionmentioning
confidence: 99%
“…Non-precipitating clouds play a more crucial role in ion deposition and aggregation than precipitating clouds do (Aleksic et al, 2009). The concentrations of soluble compounds and dissolved acids have gener-ally been reported to be much higher in cloud liquid water compared with precipitation (Błaś et al, 2008;Zapletal et al, 2007;Zimmermann et al, 2003). For example, Sun et al, (2010) found that the concentrations of ammonium, sulfate and nitrate in cloud water were at least 5.17 times higher than those in rainwater.…”
Section: Introductionmentioning
confidence: 99%
“…1995; Elias et al 1995;Mindas & Skvarenina 1995;Skvareninova & Skvarenina 2000;Elbert et al 2000;Acker et al 2002;Migala et al 2002;Herckes et al 2007;Zapletal et al 2007;Mihalikova et al 2008). We have been concerned with these problems in our previous work for example , Fisak et al (2002, Fisak et al ( , 2006a.…”
Section: Introductionmentioning
confidence: 99%